2022
DOI: 10.1051/0004-6361/202141213
|View full text |Cite
|
Sign up to set email alerts
|

Eviction-like resonances for satellite orbits

Abstract: The motion of a satellite can experience secular resonances between the precession frequencies of its orbit and the mean motion of the host planet around the star. Some of these resonances can significantly modify the eccentricity (evection resonance) and the inclination (eviction resonance) of the satellite. In this paper, we study in detail the secular resonances that can disturb the orbit of a satellite, in particular the eviction-like ones. Although the inclination is always disturbed while crossing one ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…We have also ignored meanmotion resonances, which can be important in less hierarchical systems (e.g., Hamers et al 2018). In addition, eccentricity excitation due to capture in other resonances like eviction resonances has also been studied in the literature but ignored in this study (Touma & Wisdom 1998;Vaillant & Correia 2022). Recently, it has been shown that the eccentricity of a binary in a hierarchical triple system can be excited by precession-induced resonances (Kuntz 2022).…”
Section: Analytical Theorymentioning
confidence: 99%
“…We have also ignored meanmotion resonances, which can be important in less hierarchical systems (e.g., Hamers et al 2018). In addition, eccentricity excitation due to capture in other resonances like eviction resonances has also been studied in the literature but ignored in this study (Touma & Wisdom 1998;Vaillant & Correia 2022). Recently, it has been shown that the eccentricity of a binary in a hierarchical triple system can be excited by precession-induced resonances (Kuntz 2022).…”
Section: Analytical Theorymentioning
confidence: 99%